2020
DOI: 10.3390/jcm9020407
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Options for the Treatment of Interstitial Lung Disease Related to Connective Tissue Diseases. A Narrative Review

Abstract: Interstitial lung disease (ILD) is one of the most serious pulmonary complications of connective tissue diseases (CTDs) and it is characterized by a deep impact on morbidity and mortality. Due to the poor knowledge of CTD-ILD’s natural history and due to the difficulties related to design of randomized control trials, there is a lack of prospective data about the prevalence, follow-up, and therapeutic efficacy. For these reasons, the choice of therapy for CTD-ILD is currently very challenging and still largely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 160 publications
0
65
0
2
Order By: Relevance
“…The Panther study demonstrated an increase in mortality and infections in patients with IPF treated with immunosuppressive drugs [41]. The role of immunosuppressants in usual interstitial pneumonia (UIP) in RA or CTD has not been clarified, but a better response in ILD patterns different to UIP has been suggested by some retrospective studies [42][43][44].…”
Section: Immunosuppressantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Panther study demonstrated an increase in mortality and infections in patients with IPF treated with immunosuppressive drugs [41]. The role of immunosuppressants in usual interstitial pneumonia (UIP) in RA or CTD has not been clarified, but a better response in ILD patterns different to UIP has been suggested by some retrospective studies [42][43][44].…”
Section: Immunosuppressantsmentioning
confidence: 99%
“…Therefore, RA-ILD with nonspecific interstitial pneumonia (NSIP) or organizing pneumonia (OP) patterns could have a more favorable response to immunosuppressive therapy than the UIP pattern [42][43][44].…”
Section: Immunosuppressantsmentioning
confidence: 99%
“…Nowadays, there is a growing awareness of the significant morbidity and mortality that the presence of an AD-ILD entails [ 5 , 6 , 7 ]. In this sense, several reports have been published on the diagnostic and therapeutic management of this group of diseases [ 12 , 14 , 30 ]. Most of these reports indicate the use of mycophenolate mofetil and cyclophosphamide as the main conventional immunosuppressive drugs for the treatment of patients with AD-ILD.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment choice is usually a shared decision between pneumologists and rheumatologists, based on personal experience, retrospective studies and case series. In this regard, several therapeutic options have yielded promising results, including lung transplantation as the last alternative [ 12 , 13 ]. Besides corticosteroids, cyclophosphamide and mycophenolate mofetil are the most widely used drugs among the conventional immunosuppressive drugs [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immunosuppressors are considered the mainstay of treatment for SSc-ILD, with cyclophosphamide and mycophenolate mofetil (mycophenolate) being the most widely used agents based on the results of two large randomized clinical trials (RCTs) that assessed the effect of cyclophosphamide against the placebo (The Scleroderma Lung Study-I, SLS-I) and cyclophosphamide against mycophenolate (The Scleroderma Lung Study-II, SLS-II) on lung function decline [ 6 , 7 , 8 ]. Moreover, observational studies and two small RCTs reported efficacy of rituximab in decreasing the rate of SSc-ILD progression, suggesting its use as rescue therapy in patients progressing despite treatment with cyclophosphamide and mycophenolate [ 9 ]. Recently, nintedanib, a tyrosine kinase inhibitor, was licensed in USA and Europe to treat adult patients with SSc-ILD based on the results of the SENSCIS trial, a phase III, double-blind, placebo-controlled trial that evaluated the effect of nintedanib against the placebo on the annual rate of FVC decline [ 10 ].…”
Section: Introductionmentioning
confidence: 99%